ESP STUDENTS' PERCEPTIONS TOWARDS MENTORING STRATEGY TO IMPROVE SPEAKING SKILLS - Yuyun Putri Mandasari; Eka Wulandari (Suluh Adiluhung Publisher (SAPub), 2024)
English speaking proficiency has become prominent for Midwifery Students to prepare them in the global competition of the health field. Unfortunately, they have complex problems in learning and practicing speaking, such as a lack of motivation, confidence, and vocabulary, being afraid of making mistakes, and difficult pronunciation. Mentoring strategy comes as one of the best solutions for their problems. This study aimed to explore Midwifery students’ point of view towards a mentoring strategy to help them enhancing speaking skills. A survey research with mixed methods design was employed in this research by administering a questionnaire and interview. The result indicated that the respondents had a strong attitude and positive perspective towards the mentoring program. In conclusion, it is one of the best alternative ways to be applied in the classroom and equip the students with English competency, particularly the speaking skills.